An estimated 400–800 million tons of prey are annually killed by the global spider community - Nyffeler, Martin (Naturwissenschaften, 2017)
Spiders have been suspected to be one of the most important groups of natural enemies of insects worldwide. To document the impact of the global spider community as insect predators, we present estimates of the biomass of annually killed insect prey. Our estimates assessed with two different methods suggest that the annual prey kill of the global spider community is in the range of 400–800 million metric tons (fresh weight), with insects and collembolans composing >90% of the captured prey. This equals approximately 1‰ of the global terrestrial net primary production. Spiders associated with forests and grasslands account for >95% of the annual prey kill of the global spider community, whereas spiders in other habitats are rather insignificant contributors over a full year. The spider communities associated with annual crops contribute less than 2% to the global annual prey kill. This, however, can be partly explained by the fact that annual crop fields are “disturbed habitats” with a low buildup of spider biomass and that agrobiont spiders often only kill prey over short time periods in a year. Our estimates are supported by the published results of exclusion experiments, showing that the number of herbivorous/detritivorous insects and collembolans increased significantly after spider removal from experimental plots. The presented estimates of the global annual prey kill and the relative contribution of spider predation in different biomes improve the general understanding of spider ecology and provide a first assessment of the global impact of this very important predator group.